3D surgical printing and pre contoured plates for acetabular fractures. Issue 11 (November 2016) - Chana-Rodríguez, Francisco; Mañanes, Rubén Pérez; Rojo-Manaute, José; Gil, Pablo; Martínez-Gómiz, José María; Vaquero-Martín, Javier
Abstract: We describe the methodical and possibilities of 3D surgical printing in preoperative planning of acetabular fractures showing a case of a 45-year-old with an associated transverse fracture of the left acetabulum with posterior wall fracture, with multiple fragments, and posterior ipsilateral hip dislocation, defending the do it your-self mode.